Do Refugee Camps Help or Hurt Hosts? : The Case of Kakuma, Kenya - Alix-Garcia, Jennifer; Walker, Sarah; Bartlett, Anne (Elsevier, 2018)
We combine nighttime lights data, official statistics, and new household survey data from northern Kenya in order to assess the impact of long-term refugee camps on host populations. The nighttime lights estimates show that refugee inflows increase economic activity in areas very close to Kakuma refugee camp: the elasticity of the luminosity index to refugee population is 0.36 within a 10 km distance from the camp center. In addition, household consumption within the same proximity to the camp is 25% higher than in areas farther away. Price, household survey, and official statistics suggest that the mechanisms driving this positive effect are increased availability of new employment and price changes in agricultural and livestock markets that are favorable to local producers.